Malvinas: design and experiences of the return. The "Centro de Recuperación del Personal de la Fuerza" (June-July 1982) (Quinto Sol, 2021)
Between June 9th and July 4th, 1982, the "Centro de Recuperación del Personal de la Fuerza" operated within Campo de Mayo, one of the places designed by the Argentinian Army to receive and isolate a few thousand officials, sub-officers and conscripted soldiers for a few days after returning from the Falklands War. Even if it is an experience limited in time and space, the hypothesis of this work is that its intensive study provides valuable aspects on at least two dimensions. On the one hand, it grants information on how the war experience began to be interpreted within the Argentine Army and how, in this context, control mechanisms and their borders were reimagined. On the other hand, the experience of the CRPF also allows a better understanding of how some sectors of Argentine civil society in mid-1982 related in general to the dictatorship and in particular to the war.
Keywords: Falklands war; reception; postwar period; Argentine Army